Sebuah PERANCANGAN SISTEM INFORMASI PENGENALAN KEBUDAYAAN SUKU MOI BERBASIS WEB PADA LEMBAGA ADAT MALA MOI KOTA SORONG PROVINSI PAPUA BARAT - Iriene Surya Rajagukguk (LPPM Poltek ST Paul, 2022)
The Mala Moi Traditional Institute is one of the traditional and cultural institutions under the auspices of the Sorong City and Regency government. In the delivery of information regarding the introduction of the culture of the Moi Tribe is not conducive. This is due to the lack of information about the ethnicity and culture of the Moi Tribe. This resulted in the culture of the Moi Tribe being increasingly depleted by modernization. Therefore, it is very necessary to create a web-based information system that can help overcome these problems. The purpose of this study is to design a web-based information system for the introduction of the Moi Tribe culture that provides information about the Moi Tribe. The system data collection method used is the Waterfall method with the stages of requirements analysis, system design, program code writing, program testing, implementation, and program maintenance. The result of this research is that a web-based cultural introduction information system can help the Mala Moi Traditional Institute in introducing the culture of the Moi Tribe.